Horticultural and physiological aspects of vigour control in apricot (Prunus armeniaca L.) under orchard and controlled environment conditions : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy (Ph.D) in Pomology and Fruit Tree Physiology at Massey University New Zealand - Arzani, Kazem (Massey University, 1994)
In the absence of dwarfing rootstocks for apricot, techniques which reduce vegetative growth are important in the orchard management system. Studies were conducted in the orchard and in controlled environment (CE) rooms in order to explore the horticultural and physiological responses of apricot (Prunus armeniaca L.) to some vigour control techniques. In the orchard in the humid climate of Palmerston North, New Zealand, five-year-old vigorous 'Sundrop' apricot trees on 'Golden Queen' peach seedlings trained on Tatura trellis at 1000 or 2000 tree ha-1 were used. The objectives were: a). to evaluate the trees' responses to 0.5 and 1.5 g. tree-1 soil applied Paclobutrazol (PBZ), dormant root-pruning and regulated deficit irrigation (RDI); b). to identify osmotic adjustment in fruits and leaves in response to internal water stress. Two-year-old 'Trevatt' apricot in an aeroponic system in CE rooms were used with the objectives: a). to examine the effects of root cytokinin and endogenous ABA on shoot growth and whole plant physiology; b). to study the mechanism of adaptation to high water stress. In the orchard all treatments reduced vegetative growth. PBZ was more effective than the other treatments, and the lower rate (0.5 g. tree-1) when applied annually gave more uniform growth reduction. The root-pruning and RDI had less effect, particularly in the second season of study. The deep soil, together with low temperature and evaporation, high rainfall and humid conditions during winter and early spring were limiting factors for RDI. The inhibitory effect of root-pruning was more persistent on wider spaced trees. In close planted trees root length density (RLD) declined with increasing depth, but roots were observed to 1.6 m explored soil depth. Root-pruning increased RLD, but no treatments effect was observed on root weight density (RWD) in the explored soil volume. PBZ increased dry matter partitioning into crop in both seasons on close spaced trees, and fruit growth and final fruit size were increased without any detrimental effect on fruit quality. In the second year PBZ advanced flowering by 2-4 days, and increased fruit set, final fruit number, crop density and yield efficiency. In general RDI had no negative effects on flowering, fruiting, yield and final fruit size. In the second year it generally enhanced flowering, fruit set and fruit number. Root-pruning did not affect other flowering and yield parameters, but reduced fruit size in the first season. There was some evidence of advanced fruit maturity and increased total soluble solids by all applied treatments. Generally fruiting characteristics were improved, and vegetative growth reduced, more by PBZ than by root-pruning and RDI. PBZ treated trees had the same water status as controls. Their net CO2 assimilation rate (A) and stomatal conductance (gs) were improved, and from later stage I and during stages II and III of fruit growth fruit carbohydrates were increased. RDI and root-pruning increased net CO2 assimilation rate (A) and stomatal conductance (gs) on some occasions. Root-pruned trees developed an increased internal water deficit in the leaves and fruits especially at the time of highest water demand during fruit stage III. There was evidence on occasions in RDI and root-pruning of osmotic adjustment in leaves and fruits maintaining turgor (ψp). An aeroponic system with intermittent misting gave good control of plant water stress. When water stress was developed gradually plants were able to maintain their turgor at high internal water deficit (-2.2 and -3.0 MPa of ψxylem and ψ1 respectively). Osmotic adjustment occurred in both partially and fully expanded leaves of all treatments, BAP combined with water stress showed bigger osmotic adjustment. Water stress reduced vegetative growth, and increased root:shoot ratio. Shoot tip ABA increased as water stress increased. BAP reduced the growth inhibition and rise in shoot ABA of water stressed plants, maintained net CO2 assimilation rate (A) and stomatal conductance (gs), and increased root:shoot ratio.
Keywords: Apricot; Prunus armeniaca; Apricot growth; Orchard management; Sundrop apricot; Trevatt apricot; Water stress; Abscisic acid (ABA)